An analysis of the efficiency and competitiveness of Vietnamese port system - Thai, Vinh Van (2012)
Ports, as one of the important links between different modes of transport within the logistics chain, have special essence since their efficiency and competitiveness will certainly have an impact on the chain, and hence the national and regional economy. Vietnam, as a developing country gradually integrating into the regional and global economy, is rationalizing its economic sectors, including transportation. In this environment, ports play a vital role for the purpose of achieving comparative advantages in the international market. However, the Vietnamese port system is burdened with outdated work practices, low efficiency and poor competitiveness compared to other ports in the region. This paper identifies some of the problems in the Vietnamese port system and proposes strategies to address them.